Peer-based Health Educator sebagai Alternative Approach Pendidikan Kesehatan Reproduksi Remaja di Sekolah - Kartika Ratna Pertiwi; Siti Mariyam (Humanism: Journal of Community Empowerment (HJCE), 2019)
Peer education is a communication approach which targets not only to provide information but also to help teenagers being able to solve problem, make decision and possess healthy sexual behavior. This community programme aimed to develop peer-based health educator as an alternative approach in reproductive health education for teenagers in senior high school SMA N 1 Prambanan, Yogyakarta. The program consisted of three steps: 1) preliminary actions to select and train university students as the mentors, 2) seminar on reproductive health and peer education, 3) focus group discussion, whereby mentors and students discussed and did role play on interesting cases of sexual health in school setting, and 4) follow up program whereby selected student tutors created and implemented their own program of choice. Our program demonstrated an increase of student knowledge in reproductive health (3%) and an increase of mentoring skill (50%) as well as an increase in student tutors’ ability of handling cases and being problem solver in sexual health cases (78.13%). The success of this program was due to the school support, enthusiasm from the participants and personal approach from all committee members.  In the future, we hope that all student tutors could expand their knowledge and improve their skill, to establish a healthy sexual health community and also with more involvement from the school teachers in the program. Keywprds: reproductive health, school, tutor, peer, healthy sexual behavior